BO‘LAJAK KIMYO O‘QITUVCHILARNI INNOVATSION TA’LIM TEXNOLOGIYALARI VOSITASIDA TAKOMILLASHTIRISH METODIKASI - Ajieva, M.B.; Dauekeeva, G.U. (SCIENCE and SOCIETY, 2024)
This article is about the use of innovative pedagogical technologies in the improvement of chemistry classes with the help of pedagogues, as well as the purposeful and effective use of interactive methods in classes, team communication, logical thinking, synthesis of ideas, and the ability to analyze. serves to create a wide range of opportunities for recipients. Information was given on how to use pedagogical technologies in the teaching of chemistry – «Sinkwain», «Brainstorming», «Networks», «Cluster» methods during the lesson.